Rimonabant: From RIO to Ban - Amir H. Sam; Victoria Salem; Mohammad A. Ghatei (Journal of Obesity)
Endocannabinoid antagonism as a treatment for obesity and the metabolic syndrome became a hugely anticipated area of pharmacology at the start of the century. The CB1 receptor antagonist Rimonabant entered the European mass market on the back of several trials showing weight loss benefits alongside improvements in numerous other elements of the metabolic syndrome. However, the drug was quickly withdrawn due to the emergence of significant side effects—notably severe mood disorders. This paper provides a brief overview of the Rimonabant story and places the recent spate of FDA rejections of other centrally acting weight loss drugs entering Phase 3 trials in this context.